Women's participation in the Malaysian parliament : a comparative analysis in the light of shura principles - Mohd Kamarul Amree bin Md. Sarkam (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
Malaysia is considered one of the most progressive countries in the Muslim world steadily moving towards enhanced political stability, general standard of living, technological advancement, and an integrated multi-cultural, multi-ethnic and multi-religious society. All of these aspects of development cannot be realized without a stable political foundation symbolized in the opening of the Malaysian Parliament on 31 August 1957. The Malaysian Parliament constitutes a democratic political institution which synchronizes the aspirations of a united Malaysian people. In accordance with the function of the Malaysian Parliament as a chamber of surveillance and admonition, the representation and participation of women which make up half of the population is an essential prerequisite of the democratic principle. In fact, Malaysian women representatives contribute significantly in terms of insightful ideas, concrete arguments, and affirmative actions towards resolving national problems in general and women's problems in particular. However, the participation of women in the Malaysian Parliament tends to remain undervalued and underappreciated by some factions in society who ascribe to women in general certain physical and intellectual weaknesses which render them unfit for such positions or even suppose that women should not be involved in public affairs at all and tend to their homes and families instead. Such negative preconceptions and stereotypes undermine the women's dignity and continuously question their capability and thus reject the contributions of half of the populace towards achieving Malaysian excellence as a nation. A systematic comparative study is highly needed in order to identify solutions to this obstacle which is based on misconceptions. Islamic tradition does not prohibit the active participation of women in the public sphere but is actually embedded in shËrÉ principles. The shËrÉ or Islamic law is based on the divinely revealed Qur'Én and the Prophetic Sunnah and thus a model guide to attain human perfection. The Malaysian Parliament, however, is a man-made institution infused by western values and principles exposed to ambiguity and imperfection. Thus, the participation of women in the Malaysian Parliament should not be based on western notions of equality but on Islamic principles. Although Parliament is an originally western political institution, Islamic tradition entails the notion of mutual consultation (shËrÉ). Likewise, in Islam women are entitled to voice their opinions independently, exchange ideas, and provide services to the people. Muslim jurists have differed in opinion whether women can participate in both institutions; the traditional shËrÉ and parliament. This research discusses arguments for and against the participation of women in political affairs based on the primary and secondary sources of Islamic law with the aim to propose a moderate viewpoint and solution. A comparative study between the two institutions in general and women's participation in particular provides the basis for a subsequent evaluation of existing shËrÉ principles as to whether women should participate in the Malaysian Parliament or not.